(untitled) (World Bulletin of Management and Law, 2022)
The economic institution is the core of the economic activity and the preferred financial management job for making profits and wealth in society. It also consists of a group of interconnected human, financial, and material means, in order to accomplish a certain objective. Undoubtedly, the perfect management in terms of planning, organization, direction and control represents its efficiency and continuity. The institution performs several and varied functions, including: the production, the human resources, and the financial jobs. Despite the significance of these varying jobs in the organization, the latter, the financial job, is one of the basic jobs. It determines the future of the institution, the extent of its continuity, financial structure and other tasks. It plays a crucial role in providing funds to finance aspects of activity that determine the future of the institution, its continuity, financial structure, and other jobs. It also plays a crucial role in providing funds to finance various aspects of activity .